Benefits of Unmanned Aerial Vehicles in the South African Construction Industry: Exploratory Factor Analysis - Phuriwa, Unarine Ronaldo; Liphadzi, Murendeni; Oguntona, Olusegun Aanuoluwapo; Aigbavboa, Clinton (International Journal of Sustainable Construction Engineering and Technology, 2025)
Construction is a toxic industry with numerous difficulties such as time and budget overspending to mention a few. Despite these challenges, the construction industry (CI) is at the centre of the development of any economy. Thus, it is crucial to identify and understand the different technologies that are available to assist in growing the sector. Unmanned aerial vehicles (UAVs) are among the novel innovations that can lessen the difficulties encountered in the CI. Thus, the purpose of this study is to assess and emphasise the significance of UAVs. The study uses a survey methodology, and a standardized questionnaire was used to evaluate South African built environment experts. SPSS was used for the questionnaire’s analysis, and the data was presented using principal component, t-test, and mean score for statistics testing. The results revealed that the application of UAVs on construction projects is beneficial to construction professionals. The application of UAVs for high-quality image capture, offering real-time information prevents injuries and accidents on site. It is anticipated that the findings will inform the many stakeholders involved in construction about the advantages of implementing the usage of UAVs for CI. Additionally, it will enhance the current body of knowledge in the CI and the research field. It is anticipated that this investigation will contribute to the CI’s adoption and application of innovation technologies.